Komposisi Umur Tanaman Ideal di Perkebunan Kelapa Sawit - Iput Pradiko; Dhaffa Agung Thirafi; Desra Sahputra; M. Yusuf Muslim; Agus Eko Prasetyo; Muhayat Muhayat (Pusat Penelitian Kelapa Sawit, 2026)
Age composition of oil palm is a key aspect of sustainable plantation management. This study aims to identify the ideal age composition that ensures high and stable production over the long term. A 25-year planting cycle simulation was conducted across 13 age composition scenarios, and analyzed using a Multi-Criteria Decision Analysis (MCDA) framework with the Multi-Attribute Utility Theory (MAUT) method. The results indicate that the ideal age composition consists of 12% Immature Palm (TBM, 0-3 years), 20% Mature I (TMD, 4-8 years), 20% Mature II (TMR, 9-13 year), 28% Mature III (TDW, 14-20 year), 16% Old Palm (TTA, 21-25 years), and 4% Replanting (TU, >25 years). This composition achieves an optimal average palm age (RUT) of approximately 13.22 years, along with high production and low fluctuation. Furthermore, the study highlights the importance of systematic and sustainable replanting planning to maintain a balanced age structure, especially in plantations with suboptimal age compositions. This strategy is key to ensuring long-term production stability and efficiency in oil palm plantation.